Investigation of Fenugreek (Trigonella foenum-graecum) Seed Extract in Combating Glucotoxicity via Modulation of the Canonical Wnt Signaling Pathway: In Vivo and In Silico Approach - Sadia , Humaira; Hossain, Md Monir; Ahmed , Md Khurshid; Sultana, Razia (Bangladesh Pharmaceutical Journal, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by prolonged hyperglycemia, in which glucose reacts covalently with plasma proteins through a non-enzymatic process known as glycation. This leads to the formation of advanced glycation end-products (AGEs), which play a central role in the development of diabetic complications, including osteoporosis. These accumulated AGEs disrupt the canonical Wnt signaling pathway, thereby increasing bone resorption and reducing bone formation, ultimately leading to osteoporosis. This present study has been designed to explore the antidiabetic potential of Fenugreek (Trigonella foenum-graecum) seed extract (TSE) in inhibiting AGEs formation. Based on the study results, TSE at two different doses (200 and 700 mg/kg/day) significantly lowered the blood glucose levels in methylglyoxal (MGO)-induced diabetic mice model. Since MGO acts as a key precursor in the glycation process, these results suggest that TSE may help to slow glycation and AGEs accumulation. Furthermore, molecular docking analysis also revealed that two compounds of TSE such as, Yuccagenin and Diosgenin act as key bioactive components to exhibit the strong binding affinities (− 9.8 kcal/mol) with Sclerostin, indicating its potential role in reducing the bone degradation and preventing diabetes-associated osteoporosis. Bangladesh Pharmaceutical Journal 29(1): 40-52, 2026 (January)